Gender Violence and Work: Reckoning with the Boundaries of Sex Discrimination Law - Goldscheid, Julie (Columbia Journal of Gender and Law, 2008)
“It is uncontroverted . . . that Hossack was terminated because management feared her husband’s threats and that he might very well cause workplace disruption in the future … [consequently] no reasonable jury could find that the defendant terminated [her] employment because she is a woman.” Workplace inequality based on sex, as well as discrimination based on other protected characteristics, persist notwithstanding several decades of antidiscrimination laws. An extensive body of scholarship examines this and related forms of persistent inequality and identifies a number of approaches, such as reforms that would target cognitive bias, entrenched structures of decision-making, and unconscious discrimination, to redress what has been termed “second generation” employment discrimination. This Article takes that project in an unexplored direction. The treatment of domestic and sexual violence survivors at work often reflects a subtle form of sex discrimination that antidiscrimination law currently fails to adequately reach. This subtle bias inevitably informs and distorts workplace decisions involving domestic and sexual violence victims. This Article proposes a “second generation” discrimination solution that requires employers to engage in an interactive process with survivors of gender- based violence before taking adverse actions against them. This would bring the issue to the surface, reduce stigma, and ensure that any adverse employment action is based on legitimate reasons, as opposed to subtle biases. By identifying and accounting for this nuanced manifestation of sex discrimination, antidiscrimination law can more fully advance its goal of eliminating sex-based inequality at work.